The Influence of Word of Mouth and Perceived Value on Parents' Decisions to Choose Kids Republic Jakarta School - Julio, Muhammad Akbar; Shihab, Muchsin Saggaff (PT Inovasi Pratama Internasional, 2024)
This study aims to analyze the influence of Word of Mouth (WoM) and perceived value on parents' decisions to enroll their children at Sekolah Kids Republic Jakarta, an early childhood education institution (PAUD) located in Jakarta. The population for this study comprised 204 parents of students currently enrolled at Sekolah Kids Republic Jakarta. A sample of 68 parents was selected using a sampling technique with a 10% margin of error. The analysis used the Partial Least Squares Structural Equation Modeling (PLS-SEM) technique. The study yielded the following findings: (1) Perceived value has a significant and dominant influence on parents' decisions in choosing Sekolah Kids Republic Jakarta; (2) Word of Mouth (WoM) has a relatively weak and statistically insignificant influence on these decisions; and (3) The combined effect of WoM and perceived value moderately explains the variance in parents' decisions, supporting the hypothesis that both variables together significantly influence decision-making, with perceived value playing a more dominant role.